Undifferentiated Pleomorphic Sarcoma Of The Face: A Rare And Challenging Dermatologic Presentation - Zulfan Zulfan; Eva Krishna Sutedja; Endang Sutedja; Kartika Ruchiatan; Yuri Yogya; Yogi Faldian; Reiva Farah Dwiyana; Retno Hesty Maharani (Journal of Innovative and Creativity, 2025)
Undifferentiated pleomorphic sarcoma (UPS) is a rare and aggressive soft tissue malignancy, accounting for less than 1% of all soft tissue sarcomas. It is characterized by a high risk of metastasis and local recurrence, with diagnosis dependent on histopathological and immunohistochemical findings. This case report presents a rare instance of UPS and highlights the diagnostic complexity associated with its atypical presentation. A 48-year-old woman presented with pruritic, erythematous lesions on the forehead and a longstanding, hyperpigmented lesion on the left cheek. The forehead and ear lesions were unresponsive to topical treatments. Physical examination revealed multiple hyperpigmented macules and nodules with sanguine crusts. Histopathological examination showed a connective tissue stroma infiltrated by polymorphic cells, including lymphocytes, histiocytes, and plasma cells. Immunohistochemical analysis revealed focal positivity for CD31, CD34, CD68, and Ki-67, with negativity for CK, CD45, CD117, and Chromogranin. These findings were consistent with UPS. Radiologic imaging suggested pulmonary metastasis, and a secondary bacterial infection was identified. The patient was started on mupirocin for the secondary infection. Due to suspected pulmonary metastasis, surgical excision and radiotherapy were not pursued, and she began doxorubicin-based chemotherapy. Unfortunately, the patient passed away during the second cycle of chemotherapy. UPS is a rare and aggressive sarcoma that presents diagnostic challenges. Despite treatment, the prognosis remains poor due to its metastatic potential and limited response to conventional therapies. Keyword: undifferentiated pleomorphic sarcoma, diagnostic challenges, immunohistochemistry